An analytical solution for the coupled heat and mass transfer during the freezing of high-water content materials - Olguin, Mariela Carina (2008)
The coupled problem of heat and mass transfer during the solidification of high-water content materials like soils, foods, tissues and phase-change materials is developed. Assuming quasi-steady heat conduction in the frozen region, the system leads to a set of coupled ordinary differential equations. The model takes into account the influence of material characteristics and process variables on the advance of the freezing and sublimation fronts, temperature and water vapour profiles and weight loss. It was validated against the analytical solution of the freezing (without surface ice sublimation) of a semi-infinite medium and was extensively used to perform a parametric study.